List of Pictures - Dezső, Krisztina; Lengvári, István; Méreg, Martin; Pálmai, Dóra; Polyák, Petra; Varga, Krisztina (Per Aspera ad Astra, 2024)
List of images published in Per Aspera ad Astra 2023/1-2.